Evaluation of an interactive web-based programme on relapse management for people with multiple sclerosis (POWER@MS2): study protocol for a process evaluation accompanying a randomised controlled trial - Christoph Heesen; Sascha Köpke; Lisa Wenzel; Jutta Scheiderbauer; Markus van de Loo; Anne Christin Rahn (BMJ Open)
Introduction Process evaluations accompanying complex interventions examine the implementation process of the underlying intervention, identify mechanisms of impact and assess contextual factors. This paper presents the protocol for a process evaluation conducted alongside the randomised controlled trial POWER@MS2. The trial comprises the evaluation of a web-based complex intervention on relapse management in 188 people with multiple sclerosis conducted in 20 centres. The web-based intervention programme focuses on relapse treatment decision making and includes a decision aid, a nurse-led webinar and an online chat. With the process evaluation presented here, we aim to assess participants’ responses to and interactions with the intervention to understand how and why the intervention produces change.Methods and analysis A mixed methods design is used to explore the acceptance of the intervention as well as its use and impact on participants. Participants are people with multiple sclerosis, neurologists, nurses and stakeholders. Quantitative semistandardised evaluation forms will be collected throughout the study. Qualitative semistructured telephone interviews will be conducted at the end of the study with selected participants, especially people with multiple sclerosis and neurologists. Quantitative data will be collected and analysed descriptively. Based on the results, the qualitative interviews will be conducted and analysed thematically, and the results will be merged in a joint display table.Ethics and dissemination The process evaluation has received ethical approval from the Ethical Committee of the University of Lübeck (reference 19–024). Findings will be disseminated in peer-reviewed journals, at conferences, meetings and on relevant patient websites.Trial registration number NCT04233970.